Бром в почвах Томской области - Перминова Т. А. Татьяна Анатольевна; Барановская Н. В. Наталья Владимировна; Ларатт Б. Бертран; Жорняк Л. В. Лина Владимировна; Судыко А. Ф. Александр Федорович (2017, 2017)
Заглавие с титульного листа